Health transitions among Filipino older people - Cruz, Grace T. (Quezon City Population Institute, University of the Philippines Diliman, 2005)
The study examines the functional health status of Filipino older people. Using data from the 1996 Philippine Elderly Study, results provide a baseline estimate of the Active Life Expectancy (ALE) among those 60+ years and its gender differentials. Capitalizing on the first available panel data on elderly in the country, health transition patterns and its determinants as well as the ALE differentials across selected socio-economic groups are also examined. Findings demonstrate a significant gender pattern in ALE with the females more likely to outlive their male counterparts although they can expect to live a greater part of that life in a state of physical disability. Controlling for initial health status however reveals the greater vulnerability of the unhealthy males. Heterogeneity in ALE across the socioeconomic status groups underscore the disadvantageous position of those in the higher socioeconomic bracket particularly those who survive to advance old age. Health transition results also demonstrate a significant proportion of recovery in functional health with the females more likely to experience disability and to remain in an unhealthy state compared to the males. A complex set of socio-demographic and health risk behaviors are found to impinge on their health transition and their mortality experiences suggesting the possible areas of intervention.
Thesis
Keywords: Older people -- Health and hygiene -- Philippines; Aging -- Health aspects -- Philippines